EFFICACY OF BARIATRIC SURGERY IN THE TREATMENT OF PATIENTS WITH METABOLIC SYNDROME IN ASSOCIATION WITH GASTROESOPHAGEAL REFLUX DISEASE - Khakimov, M.SH.; Khamdamov, A.B. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
The term "bariatric" surgery, derived from the Greek word baros, meaning weight, defines surgical procedures aimed at significant weight loss. Accordingly, the goals of bariatric surgery initially evolved around achieving substantial, sustainable weight loss. Weight loss is only one of the outcomes of such an operation. Bariatric surgery may be associated with significant other health benefits, including improving or normalizing hyperglycemia. Hyperlipidemia, blood pressure, obstructive sleep apnea, and improved quality of life. Due to the broad benefits of weight loss and the growing evidence that some bariatric surgeries cause metabolic changes that cannot be fully explained by their effects on body weight alone, the name "bariatric metabolic surgery" is becoming more appropriate.